A general strategy for enabling Fe3O4 with enhanced lithium storage performance: Synergy between yolk-shell nanostructures and doping-free carbon. (20th January 2021) - Na, Zhaolin; Yao, Ruifang; Yan, Qing; Wang, Xinran; Sun, Xudong; Wang, Xuxu
Highlights: The doping-free carbon shell was constructed through the pyrolysis of acetone. The void in Fe3 O4 @C was tuned continuously with the variation in the etching time. The Fe3 O4 @C showed excellent cycling stability and great rate capability. This carbon coating strategy could motivate the development of LIBs anode material. Abstract: Transition metal oxides such as Fe3 O4 have been widely explored as the anode material for lithium-ion batteries (LIBs). The construction of yolk-shelled structure and doping-free carbon shell is considered as an ideal strategy to advance their lithium storage properties. Herein, a facile and scalable strategy is provided to fabricate the carbon shell on the surface of Fe3 O4 nanocubes. Then, a series of yolk-shelled Fe3 O4 nanocubes are synthesized through etching-in-a-box strategy. Thanks to the doping-free carbon shelled and the void between the Fe3 O4 and carbon, the yolk-shelled Fe3 O4 nanocubes electrode as anode materials for LIBs display a high specific capacity (910 mA h g −1 at 100 mA g −1 ) and excellent cycle stability (451 mA h g −1 after 2000 cycles at 5 A g −1 ). The method to produce doping-free carbon shell is easy and efficient and can be readily extended to design other high-performance LIBs anode materials. Graphical abstract: A series of yolk-shelled Fe3 O4 @C nanocubes are synthesized through a facile carbon coating process by utilizing acetone as carbon source. The void in Fe3 O4 @C is tuned continuously with the variation in the etching time. When evaluated as electrode materials for lithium-ion batteries, the nanocomposite exhibits large reversible capacity, excellent cycling stability and great rate capability. Image, graphical abstract